Implementasi Profit and Loss Sharing Petani Padi Ditinjau dari Perspektif Ekonomi Islam - julio basuki herlangga (ITB AAS INDONESIA Surakarta, 2021)
Abstrak In Kaibeso, there is a profit sharing system in agriculture done among paddy farmers, and it is called paron system. Paronsystem is used by Kadibeso people as a way to share the work profit between farmers and rice field owners. This system has been preserved among farmers, especially those in Kadibeso village. This system,which is similar to profit sharing system in Islamic economy,becomes the accounting system for capital owners (rice field) and the cultivators. In Islamic economy system, this cooperation between capital owners (rice field) and the cultivators is called Muzara’ah and Mukhabarah.The metod used in this research is qualitative method- a research done to understand the phenomena experienced by the subject of the research such as behavior, perception, mitivation, and action. The data used in this reseacrh consist of primary and secondary data.Paron system is line with Islamic economic system because it does not lease ice field but give the right to farmers to cutivate. It is already in line with Al-Quran and Haditd. Key word : Paron, Islamic economy, Muzara’ah, Mukhabarah.